2023
DOI: 10.19128/turje.1182732
|View full text |Cite
|
Sign up to set email alerts
|

Academics’ perspective on out-of-school learning environments

Abstract: This study aims to ascertain academicians' opinions about out-of-school learning, awareness of it, and competency to plan learning activities in such situations for the purpose of teaching in out-of-school learning environments (OSLEs). The research group of this study, which was conducted as a case study, consists of 56 academics in the physics, chemistry, biology, and science education programs of education faculties in Türkiye. The Out-of-School Learning Environments Regulation Scale and a form containing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…According to the results of the study, science centers and museums rank first among the most preferred environments. Aslan et al (2023) conducted a study involving experienced and inexperienced faculty members to investigate out-of-school learning environments. Their findings indicated that natural and thematic parks, science and research centers, as well as industrial organizations, are commonly suggested as effective LEs for out-of-school learning experiences.…”
Section: Noncompatibility 64%mentioning
confidence: 99%
“…According to the results of the study, science centers and museums rank first among the most preferred environments. Aslan et al (2023) conducted a study involving experienced and inexperienced faculty members to investigate out-of-school learning environments. Their findings indicated that natural and thematic parks, science and research centers, as well as industrial organizations, are commonly suggested as effective LEs for out-of-school learning experiences.…”
Section: Noncompatibility 64%mentioning
confidence: 99%